Impact of Workplace Bullying in Universities Teachers: A Correlational Study in Balochistan, Quetta - Manzoor, Annam; Rose, Samreena (Annals of Human and Social Sciences, 2025)
The purpose of this research was to examine the relationship between workplace bullying and job satisfaction. Since there has been a lot of work done in this field but this study aims to explore this relationship among universities teachers of Quetta. Workplace bullying is threatening and unusual acts at a workplace which are harmful for the employees leading to many worst consequences such as lower job satisfaction. For this study a sample of (n= 250) universities teachers was collected through NAQ-R and JSS and correlation was found using SPSS. The results showed a negative relationship between workplace bullying and job satisfaction. Findings depicts a need for the saved workplace environment so the employees can do better at their jobs. For this purpose meaningful policies should be made for the protection of teachers as well as awareness should be spread about workplace bullying.